2009
DOI: 10.1002/jbm.b.31496
|View full text |Cite
|
Sign up to set email alerts
|

UV curable polyester polyol acrylate/bentonite nanocomposites: Synthesis, characterization, and drug release

Abstract: Polyesterpolyolacrylate/bentonite nanocomposites, capable of in situ photo polymerization, were synthesized and characterized. The organically modified bentonite clay was prepared by an ion exchange process, in which sodium ions were replaced by alkyl ammonium ions. Organo modification of bentonite was confirmed from X-ray diffraction and fourier transform-infrared data. Microstructures were characterized by XRD data and transmission electron microscopy (TEM). Both XRD data and TEM images of polyester polyol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…There are other reports, which provided insight into the improvement of biodegradability, cell metabolic activity, release characteristics, microbial protection, equilibrium swelling, in vivo biocompatibility with minimal inflammation, and mechanical properties of various copolymer/nanoclay composite films. Examples are chlorhexidine acetate loaded PU/MMT films, [ 81b ] laponite/mafenide/alginate films, [ 90 ] sulfamethoxazole and diclofenac sodium embedded polyester polyol acrylate/bentonite nanocomposite films [ 91 ] and soy protein/MMT films for ofloxacin drug release. [ 92 ] The above‐mentioned findings suggested that the intercalated nanoclay morphology is capable of loading high amounts of drug and yielding a more prolonged release compared to that of the exfoliated structure.…”
Section: Biomedical Applications Of Copolymer/clay Nanocompositesmentioning
confidence: 99%
“…There are other reports, which provided insight into the improvement of biodegradability, cell metabolic activity, release characteristics, microbial protection, equilibrium swelling, in vivo biocompatibility with minimal inflammation, and mechanical properties of various copolymer/nanoclay composite films. Examples are chlorhexidine acetate loaded PU/MMT films, [ 81b ] laponite/mafenide/alginate films, [ 90 ] sulfamethoxazole and diclofenac sodium embedded polyester polyol acrylate/bentonite nanocomposite films [ 91 ] and soy protein/MMT films for ofloxacin drug release. [ 92 ] The above‐mentioned findings suggested that the intercalated nanoclay morphology is capable of loading high amounts of drug and yielding a more prolonged release compared to that of the exfoliated structure.…”
Section: Biomedical Applications Of Copolymer/clay Nanocompositesmentioning
confidence: 99%
“…Montmorillonite has been applied with acrylic acid and its derivatives to design a newly structured drug carrier system (Lee and Chen 2004;Thatiparti et al 2010;Bhattacharya et al 2011;Hosseinzadeh et al 2011). One interesting approach is to polymerize acrylic acid monomers in a montmorillonite suspension, rather than mixing poly(acrylic acid) with montmorillonite ( Fig.…”
Section: Poly(acrylic Acid) Formulationsmentioning
confidence: 99%
“…They reported that gel strength of the prepared hydrogel increased and release of a cationic drug decreased. Moreover, similar to alginate film, incorporating montmorillonite increased tensile strength and decreased degradation and drug release rates of a polyester polyol acrylate-based film (Thatiparti et al 2010). Polyamide and polyacrylamide have also been studied as montmorillonite-mixed formulations (Kevadiya et al 2013;Salahuddin et al 2014).…”
Section: Poly(acrylic Acid) Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to resolve the above shortcomings of pure polymer or clays in drug delivery system, new strategies are reported that clays have been introduced into polymer by different methods 10–12. It was found that the introduction of versatile inorganic materials could not only remedy some flaws of the neat polymers but also often endow them with novel properties 13, 14.…”
Section: Introductionmentioning
confidence: 99%